Evaluation of Distance Measures for Multi-class Classification in Binary SVM Decision Tree - Madzarov, GJorgji; GJorgjevikj, Dejan (Springer Berlin Heidelberg, 2010)
Multi-class classification can often be constructed as a generalization of binary classification. The approach that we use for solving this kind of classification problem is SVM based Binary Decision Tree architecture (SVM-BDT). It takes advantage of both the efficient computation of the decision tree architecture and the high classification accuracy of SVMs. The hierarchy of binary decision subtasks using SVMs is designed with a clustering algorithm. In this work, we are investigating how different distance measures for the clustering influence the predictive performance of the SVM-BDT. The distance measures that we consider include Euclidian distance, Standardized Euclidean distance and Mahalanobis distance. We use five different datasets to evaluate the performance of the SVM based Binary Decision Tree architecture with different distances. Also, the performance of this architecture is compared with four other SVM based approaches, ensembles of decision trees and neural network. The results from the experiments suggest that the performance of the architecture significantly varies depending of applied distance measure in the clustering process.